Determination of wax content in crude oil. (2nd May 2016) - Rehan, Mohammad; Nizami, Abdul-Sattar; Taylan, Osman; Al-Sasi, Basil Omar; Demirbas, Ayhan
ABSTRACT: Wax deposition is one of the chronic problems in the petroleum industry. The various crude oils present in the world contain wax contents of up to 32.5%. Paraffin waxes consist of straight chain saturated hydrocarbons with carbons atoms ranging from C18 to C36. Paraffin wax consists mostly with normal paraffin content (80–90%), while, the rest consists of branched paraffins (iso-paraffins) and cycloparaffins. The sources of higher molecular weight waxes in oils have not yet been proven and are under exploration. Waxes may precipitate as the temperature decreases and a solid phase may arise due to their low solubility. For instance, paraffinic waxes can precipitate out when temperature decreases during oil production, transportation through pipelines, and oil storage. The process of solvent dewaxing is used to remove wax from either distillate or residual feedstocks at any stage in the refining process. The solvents used, methyl-ethyl ketone and toluene, can then be separated from dewaxed oil filtrate stream by membrane process and recycled back to be used again in solvent dewaxing process.